2007
DOI: 10.1196/annals.1415.012
|View full text |Cite
|
Sign up to set email alerts
|

One‐Trial In Vitro Conditioning of Hermissenda Regulates Phosphorylation of Ser‐122 of Csp24

Abstract: The regulation of the intrinsic excitability of a neuron is an important aspect of cellular and synaptic plasticity underlying learning and memory. Various voltage-dependent K(+) channels have been shown to be critical for the modification of membrane excitability. Components of the cytoskeleton have been proposed to contribute to the location, distribution, and function of diverse K(+) channels. However, the mechanisms underlying the regulation of the cytoskeleton by signaling pathways and the role of the cyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…The present results compliment our previous study showing that enhanced excitability detected after one-trial in vitro conditioning is blocked by antisense oligonucleotide-mediated downregulation of Csp24 (Crow et al 2003). Previous work has shown that Csp24 is phosphorylated by one-trial in vitro conditioning and multi-trial Pavlovian conditioning (Crow et al 1999, 2003; Crow and Xue-Bian 2000, 2003, 2007, 2010; Redell et al 2007). The depolarized shift in the activation curve of I A proposed to contribute to one-trial conditioning-dependent enhanced excitability is blocked by preincubation of sensory neurons with Csp antisense oligonucleotide (Yamoah et al 2005).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The present results compliment our previous study showing that enhanced excitability detected after one-trial in vitro conditioning is blocked by antisense oligonucleotide-mediated downregulation of Csp24 (Crow et al 2003). Previous work has shown that Csp24 is phosphorylated by one-trial in vitro conditioning and multi-trial Pavlovian conditioning (Crow et al 1999, 2003; Crow and Xue-Bian 2000, 2003, 2007, 2010; Redell et al 2007). The depolarized shift in the activation curve of I A proposed to contribute to one-trial conditioning-dependent enhanced excitability is blocked by preincubation of sensory neurons with Csp antisense oligonucleotide (Yamoah et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…One-trial in vitro conditioning consists of pairing the CS (Light) with the application of 5-HT to the isolated nervous system. In vitro conditioning has been shown to produce multiple stages of time-dependent enhanced excitability in sensory neurons (photoreceptors), synaptic facilitation of the monosynaptic connection between sensory neurons and interneurons, and changes in protein phosphorylation (Crow & Forrester 1991,1993; Crow & Siddiqi 1997; Crow & Xue-Bian 2000, 2002, 2007, 2010; Crow et al 1996,1997,1998,1999, 2003; Yamoah et al 2005; Redell et al 2007). …”
Section: Methodsmentioning
confidence: 99%
“…Protein kinase C influenced co-precipitation of Csp24 with actin is regulated by one-trial in vitro conditioning and recombinant Csp24 sequesters G-actin in vitro (Redell et al, 2007). The phosphorylation of Ser-122, but not Ser-49 of Csp24 is produced by conditioning procedures that result in intermediate-term and long-term intrinsic enhanced excitability, but not after procedures that result in short-term changes in excitability of sensory neurons (Crow et al, 1999; Crow and Xue-Bian, 2000, 2007). Moreover, treatment with a Csp antisense oligonucleotide (ON) before one-trial conditioning blocks intermediate-term enhanced excitability, without affecting the induction of short-term enhanced excitability (Crow et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Two phosphorylation sites on Csp24 have been recently identified using electrospray mass spectrometry. One-trial in vitro conditioning regulates the phosphorylation of Ser122, but not Ser49 of Csp24 [11]. The potential regulation of the interaction between 14-3-3 protein and Csp24 by phosphorylation was assessed by the analysis of 5-HT-dependent phosphorylation of Csp24 co-precipitates generated by immunoprecipitated 14-3-3 protein.…”
mentioning
confidence: 99%
“…The nervous systems were lysed and immunoprecipitation experiments were conducted with anti 14-3-3 antibody. The immmunoprecipitates from experimental and control groups were blotted and probed with phosphospecific antibodies directed to Ser122 or Ser49 as previously described [11]. Following densitometric scanning the membranes were stripped and reprobed with anti-Csp24 antibody and scanned to provide assessment of total Csp24 levels.…”
mentioning
confidence: 99%